Ecological correlates of Spanish adolescents' physical activity during physical education classes. (November 2016) - Molina-García, Javier; Queralt, Ana; Estevan, Isaac; Sallis, James F
The public health benefit of school physical education (PE) depends in large part on physical activity (PA) provided during class. According to the literature, PE has a valuable role in public health, and PA levels during PE classes depend on a wide range of factors. The main objective of this study, based on ecological models of behaviour, was to analyse what personal, psychosocial and environmental factors were associated with moderate to vigorous PA (MVPA) during PE lessons. The sample consisted of 189 adolescents (60.8% girls; M = 16.3 years, SD = 0.7) from nine high schools. PA was assessed by accelerometer. Differences in PA behaviour between the study groups were evaluated using the analysis of variance. Mixed-model regression analysis, adjusted for clustering within schools, evaluated the relation of each independent variable with MVPA. Results indicated that MVPA represented 21.5% of the total time of the session (11.8 minutes, SD = 5.3). Boys performed more MVPA than girls (13.6 versus 10.7 minutes), specifically during sessions in which fitness activities (cardiorespiratory endurance and strength), net games and sports were performed. The highest levels of MVPA occurred among students with high physical self-efficacy perception, when lessons were held outdoors, in schools with high socio-economic status, and during lessons with cardiorespiratory fitness activities and invasion games and sports. Gender, number of students per session and PE content were significantly related to MVPA according to regression analysis. Present findings show that PA levels during the PE sessions depend on several personal, psychosocial and environmental factors.